A Route to (Het)arene-Annulated Pyrrolo[1,2‑d][1,4]diazepines via the Expanded Intramolecular Paal–Knorr Reaction: Nitro Group and Furan Ring as Equivalents of Amino Group and 1,4-Diketone - Zelina, Elena Y; Nevolina, Tatyana A; Skvortsov, Dmitry A; Trushkov, Igor V; Uchuskin, Maxim G (Journal of organic chemistry, 2019)
A straightforward protocol toward pharmacologically relevant (het)areno[x,y-b]pyrrolo[1,2-d][1,4]diazepines in good to high yields has been described. The designed approach consists of an acid-promoted furan ring opening in easily accessible N-(2-furylethyl)-2-nitroanilines or their heterocyclic analogues followed by the reductive cyclization of the corresponding nitro-1,4-diketones.